Eva Luna: Writing as History - Lynne Diamond-Nigh (Studies in 20th & 21st Century Literature, 1995)
The Bildungsroman of Eva Luna's development as a writer reflects—in a somewhat fragmented manner—important developments in Latin American literary history. Her personal quest was paralleled by an aesthetic quest, manifested in the trying on and taking off of various genres, literary movements and myths characteristic of Latin America; she even goes so far as to allude explicitly to specific authors and their individual works. Although some of these are simply lightheartedly parodied, others are reworked and reinterpreted in the light of the feminist enterprise of the past twenty-five years. Eva Luna transgresses fundamentally by having an intellectually strong, sexual, nurturing, very feminine protagonist, setting up an initial rupture with the dichotomy so clearly demarcated by Octavio Paz between "the mother and the whore." Four primary categories suggest themselves: myth and the mythic consciousness; magical realism; Boom writers; and then a miscellaneous grouping that subsumes a host of other significant literatures and literary themes: the picaresque, the neo-romantic, novels of the dictators, the ever-present conflict between civilization and barbarism, and testimonial literature.
Keywords: Eva Luna; Bildungsroman; writer reflections; Latin American literary history; genre; literary movement; myth; Boom; picaresque; neo-romantic; dictator; civilization-barbarism; testimonial literature